2009
DOI: 10.1002/jbm.b.31407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitinol surface treatments on its physico‐chemical properties

Abstract: The main purpose of this work is the study of different physicochemical treatments on Nitinol slabs and wires, with the aim of inducing the formation of a TiO(2) surface film capable of increasing the corrosion resistance of the material and of reducing the release of Ni when the Nitinol samples were immersed in simulated body fluid (SBF). To this end, a battery of measurements (surface roughness, contact angle, electrochemical corrosion, chemical analysis as a function of depth, and Ni release to SBF) has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…, Milošev & Kapun ), minimizing the adverse cytotoxic effects that would result from the release of Ni into body fluids (Pérez et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Milošev & Kapun ), minimizing the adverse cytotoxic effects that would result from the release of Ni into body fluids (Pérez et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Rutile‐based layers typically appear on NiTi alloys as a result of a high‐temperature oxidation treatment (Pérez et al . , Vojtěch et al . , Smialek et al .…”
Section: Discussionmentioning
confidence: 99%
“…The extent of leaching of Ni, which is cytotoxic, from the surfaces of NiTi implants remains a controversial issue [70,71], and several surface modifications exist to reduce this effect [4]. However, this effect is not expected to be significant in the present specimens because their specific surface area is smaller, by a factor of >4, than that of the commercially available porous NiTi spinal fusion device called Actipore™ (Biorthex Inc., Montreal, QC, Canada) [72].…”
Section: Microstructurementioning
confidence: 99%
“…Previous immersion testing demonstrated that polished Nitinol exhibits similar Ni release behavior to stainless steels and cobalt-based alloys [9,10]. Longer immersion studies (up to 6 months) found that surface treatments such as polishing and/or passivation of Nitinol wires can reduce Ni release compared to untreated controls [11][12][13][14]. Wire immersion tests have shown that thicker oxides, surface Ni particles, and Ni-rich phases contribute to increased Ni dissolution [15,16].…”
Section: Introductionmentioning
confidence: 99%